Accad Transformation in the Age of Digitalisation: Challenges and Adaptation in the Context of Islamic Finance - Yana Priyana; Sabil Mokodenseho; Yasin Ibrahim; Sahara Yarbo (West Science Islamic Studies, 2024)
This research explores the challenges and adaptations encountered by Islamic financial institutions, known as Accad, in the age of digitalization within the context of Islamic finance. Through qualitative analysis of interviews with key stakeholders, including Accad executives, Sharia scholars, regulators, and technology experts, the study elucidates the complexities of integrating digital technologies with Sharia principles while navigating regulatory, technological, and customer trust challenges. The findings reveal the multifaceted nature of digitalization challenges for Accad, ranging from Sharia-compliant product innovation to regulatory compliance and talent development. However, Accad have implemented various adaptation strategies, including collaboration with fintech firms, capacity building, customer education, and regulatory engagement, to foster innovation, enhance trust, and navigate the digital transformation landscape effectively. The research contributes to the broader discourse on digitalization in Islamic finance and offers insights for Accad and industry stakeholders to harness the opportunities presented by digitalization while upholding Sharia principles and meeting the evolving needs of Islamic finance customers.